Prinsip Periodik dalam Pemilihan Umum: Orientasi dan Implikasinya di Indonesia - Muhammad Mutawalli; Zulhilmi Paidi (Jurnal Penelitian Hukum De Jure, 2023)
The general election is one part of the practice of democracy in Indonesia. In this case, the general election is a manifestation of people's sovereignty. In general, the principles of elections include the principles of direct, general, free, confidential, honest, and fair. This study seeks to explore the legal construction related to the periodic principle of general elections which must be held periodically every five years to become a separate principle in elections. The issue of periodization in general elections really needs to be emphasized as one of the principles in general elections as the main basis for creating a cycle of replacement and filling of public positions in the state administration system. This research is a normative legal research with statutory and conceptual approaches. The results of the study confirm that the orientation of legal construction on the periodic principle has actually been expressly stated in the 1945 Constitution of the Republic of Indonesia and is based on a systematic interpretation. In this case, the orientation of the periodic aspect is part of the general election principle which is obligatory and must be implemented. This implies that the principles of general elections include the principles of direct, general, free, confidential, honest, and fair, and must be held periodically for five years. In this case, the periodic principle becomes very important to be recognized and explicitly stated in the general election law as a new principle in the technical implementation of general elections. this has implications for the implementation of elections that are inconsistent and tend to change in each implementation. Whereas in holding general elections, the periodic principle will uniformize the holding of elections simultaneously, both national elections and elections at the regional level by setting forth and affirming in the general election law that periodization is a technical principle in holding general elections in Indonesia.